Eksplorasi Kebutuhan Dan Harapan Debitur Terhadap Perlindungan Data Pribadi Dalam Industri Keuangan - Fajar Dharma Saputra; Rahmi Zubaedah (Jurnal Ilmiah Wahana Pendidikan, 2023)
In addition to exploring the demands and expectations of Indonesian debtors about the safety of their personal information, this abstract seeks to identify ways to enhance such protection. Data was gathered through interviews with borrowers from various banks as part of the qualitative technique utilized in the research. The findings indicated that debtors place a high value on the protection of their personal information when dealing with financial institutions. Debtors require assurances that third parties won't abuse their personal data. Financial institutions are also expected to improve their security protocols and personal data protection guidelines. The usage and protection of customers' personal information is another thing that customers expect financial institutions to explain in detail. Based on the findings of the study, it has been determined that financial institutions must enhance the standard of their policies and security measures in order to satisfy the demands and expectations of debtors in terms of personal data protection in the financial sector